2011
DOI: 10.1111/j.1365-2214.2011.01355.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing psychosocial well‐being of adolescents: a systematic review of measuring instruments

Abstract: Strength-based measures focusing on social emotional behavioural outcomes open up a possibility to link up assessment with promotion of psychosocial well-being, away from clinical settings and into adolescents' homes, schools and community. Future research should focus more on investigating the sensitivity and responsiveness of measuring instruments using longitudinal design in efficacy studies to assess change in adolescents' psychosocial status over extended time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 50 publications
0
58
0
3
Order By: Relevance
“…It has been estimated that up to one-third of children with ADHD have comorbid anxiety disorders [30,56,69], with median odds-ratio estimates of 3.0 (95 % CI 2.1-4.3) [23]. Results from the NIMH Collaborative Multisite Multimodal Treatment Study of Children with ADHD (MTA) demonstrated that children with ADHD and comorbid anxiety disorders responded worse to treatment and had lower scores on measures of academic achievement before treatment than children without comorbid anxiety [70].…”
Section: Adhd and Common Comorbiditiesmentioning
confidence: 99%
“…It has been estimated that up to one-third of children with ADHD have comorbid anxiety disorders [30,56,69], with median odds-ratio estimates of 3.0 (95 % CI 2.1-4.3) [23]. Results from the NIMH Collaborative Multisite Multimodal Treatment Study of Children with ADHD (MTA) demonstrated that children with ADHD and comorbid anxiety disorders responded worse to treatment and had lower scores on measures of academic achievement before treatment than children without comorbid anxiety [70].…”
Section: Adhd and Common Comorbiditiesmentioning
confidence: 99%
“…It has also been used successfully for clinical evaluation in clinical settings and as a research tool. Studies undertaken in different cultures have shown that it possesses fair reliability and good criterion and convergent validity [8-10]. Regarding the internal structure there are a large number of studies confirming the existence of the aforementioned five theoretical dimensions, using both exploratory (EFA) and confirmatory (CFA) factor analysis [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Studies undertaken in different cultures have shown that it possesses fair reliability and good criterion and convergent validity [8-10]. Regarding the internal structure there are a large number of studies confirming the existence of the aforementioned five theoretical dimensions, using both exploratory (EFA) and confirmatory (CFA) factor analysis [10,11]. However there are also discrepancies, some authors reporting three [12-15] and four factor solutions [16], and a few others who could not even find a clinically meaningful solution.…”
Section: Introductionmentioning
confidence: 99%
“…These limitations include: (a) a focus on clinical diagnosis (e.g., Conners, ) and limited examination of frequent, but problematic behaviours seen among children with subclinical problems (Goodman, ); (b) in addition, most measures focus on older children with limited screening tools available for children under age 5 (Bagner, Rodríguez, Blake, Linares, & Carter, ; Briggs‐Gowan et al., ). Furthermore, most measures: (c) take a deficit approach and do not examine behavioural competencies (Tsang, Wong, & Lo, ); (d) a focus on only one type of behaviour (e.g., Kovacs, ) or only on internalising (e.g., Spence, ) or externalising (e.g., Eyberg & Pincus, ) behaviour. The other problematic issues with the existing measures include: (e) low to moderate estimates of internal consistency (e.g., Strengths and Diffiuclites Questionnaires .51–.76; Smedje, Broman, Hetta, & von Knorring, ); (f) measures such as the Child Behavior Checklist (CBCL) (Achenbach, ) that are lengthy and time consuming for parents to complete (Goodman & Scott, ); and (g) licensing fees, which can place limits on dissemination in large population studies (e.g., Eyberg & Pincus, ; Goodman, ).…”
mentioning
confidence: 99%